Ascertaining the Evolution and Research Trends on Virtual Reality in Archery: A Bibliometric Analysis - Prasetyo, Yudik; Nugroho, Sigit; Sulistiyono, Sulistiyono; Nurhidayah, Dewi (Physical Education Theory and Methodology, 2025)
Background. The development of VR archery technology provides easiness of the faced difficulties by giving real visualization and new experience for the users. Objectives. The present study aimed to ascertain trends, evolution, research spread and research approach related to VR archery. Materials and methods. A literature analysis was conducted using bibliometric analysis approach. Harzing’s publish or perish, Mendeley desktop, and Vos viewer were applied in this present study. A total of 77 articles from 2015 to 2025 were identified in the Scopus database using the keywords “VR archery”, “Archery Virtual Reality”, and “Virtual Reality Archery”. According to study, 42 articles were found to be duplicated, 3 articles were incomplete, and 2 articles were excluded on the basis that they were not relevant to the subject. The Vos viewer was employed to analyse a total of 30 articles. In the process of sample description, it was examined the number of annual published articles, yearly citation, and articles with the most citation. A bibliometric analysis revealed research evolution each year, influencing publication and research trend related to Virtual Archery. Results. The results of co-author analysis, bibliographic coupling, keyword co-occurrence, and overlay visualization revealed collaboration among researchers, the relation among articles, and network spread forming a cluster. Furthermore, the obtained data provided detailed knowledge concerning the 11-year period of VR archery development, focusing on the formed cluster, significant publications, and collaboration network. Conclusions. The findings of this study were beneficial for researchers in developing VR archery in the future and for research practitioners in facilitating to solve difficulties through VR technology.